Pregnancy Outcome in Severe Pre-Eclampsia and Eclampsia - Qureshi, Asim Iqbal; Rasheed, Tahreem; Shafi, Shazia; Munir, Ayesha; Gul, Pari Iman; Khalid, Uzma (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To observe the impact of severe pre-eclampsia and eclampsia on the maternal and fetal outcome. Study Design: A cross-sectional prospective study. Place and Duration of the Study: The Department of Obstetrics & Gynecology, Bakhtawar Amin Trust Teaching Hospital, Multan, Pakistan from July 2020 to June 2021. Material and Methods: During the study period, a total of 121 women with either pre-eclampsia or severe pre-eclampsia were included. Age, parity, period of gestation, maternal vitals, fetal viability, findings of clinical examination, associated complications, mode of delivery and immediate maternal and fetal outcomes were recorded. SPSS version 26.0 was used for the statistical analysis. Results: During the study period, a total data of 121 patients was collected. There were 97 (80.2%) women with pre-eclampsia and 24 (29.8%) with severe pre-eclampsia. Overall, mean age was 25.4+4.1 years. Significantly more primigravida women had severe pre-eclampsia (35.1% vs. 66.7%, p=0.011). It was noted that 11 (11.3%) of the fetuses from patients with pre-eclampsia and 6 (25.0%) of the fetuses among women with sever pre-eclampsia had already intra-uterine death by the time these patients were hospitalized. Significant association of fetal status was found among women with pre-eclampsia and severe pre-eclampsia (p=0.011). The overall mean APGAR scores were significantly low for the babies born to the mothers with severe pre-eclampsia vs. pre-eclampsia (p<0.05). Significantly more women with severe pre-eclampsia were shifted to ICU following delivery in comparison to those with pre-eclampsia (75.0% vs. 19.6%, p<0.001). All 3 deaths were reported among women with severe pre—eclampsia (p<0.001). Conclusion: Primigravida women were significantly more prone to have severe pre-eclampsia. Large majority of the women with pre-eclampsia or sever pre-eclampsia delivered preterm newborns. Increased perinatal morbidity and neonatal mortality is found among women with pre-eclampsia or sever pre-eclampsia.